Band sizes of southeastern Brazilian hummingbirds - Oniki, Yoshika [UNESP] (Associação Field Ornithologists, 1996)
Aluminum numbered bands have been used to mark Brazilian hummingbirds since 1993 to obtain biological data as well as ascertain movements and longevities. Bands should be made as narrow as possible by cutting close to the numbers because of the short length of the hummingbird tarsus. Different band lengths should be determined for different species.